(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2026)
A mental disorder involves a noticeable disruption in a person’s thinking, emotional control, or actions. It is typically linked to distress or difficulties in key areas of daily life, such as work, relationships, or personal functioning. There are various forms of mental disorders, which are also commonly known as mental health conditions.Indian higher education system is loaded with academic and social distress wherein the institutions are facing a serious mental health crisis, with student suicides and psychological distress steadily rising over the last decade. This issue brings forward critical concerns about the extent to which universities acknowledge and safeguard students’ rights, address ethical challenges in providing mental health support, and either promote or limit advocacy related to mental well-being on campus. The paper explores ways to ensure student mental health in Indian universities through an approach grounded in rights and ethical principles, with particular emphasis on legal frameworks, policy measures, and institutional practices. The paper is structured around three main themes. Initially, it explores the legal rights of students to mental health care and dignity under the Constitution of India (especially Article 21) and the Mental Healthcare Act, 2017, including rights to access care, non-discrimination, confidentiality, and informed consent. It also considers how UGC guidelines and related policies on mental health and holistic well-being in higher education translate these rights into obligations for universities. Vitally, it analyses key ethical issues that arise in university mental health systems, such as breaches of confidentiality, lack of informed consent, discriminatory attitudes, unequal access to services, and the tension between student autonomy and institutional duty of care. Lastly, it looks at mental health advocacy in universities, including the roles of student groups, faculty, counsellors, administrators, and courts in demanding better services, enforcing existing rights, and building supportive, stigma-free campus cultures. Research Methodology This study follows a doctrinal (library‑based) research methodology, which is commonly used in legal and policy research. The focus is on understanding and interpreting existing legal rules, policies, judgments and official data, and then using them to analyse ethical issues and advocacy possibilities in the context of student mental health.The study uses a doctrinal legal research methodology, supported by secondary data. It involves a detailed analysis of primary legal materials (such as the Mental Healthcare Act, 2017, constitutional provisions, and key judicial decisions including SukdebSaha v. State of Andhra Pradesh), as well as policy documents issued by bodies like the University Grants Commission and relevant national education and health authorities. These are read alongside official reports and academic literature on student mental health and suicides in India. By combining doctrinal analysis with ethical reflection, the paper illustrates gaps between law and practice and proposes concrete, advocacy-oriented recommendationssuch as strengthening institutional policies, improving faculty training, empowering student-led initiatives, and enhancing accountability mechanisms. The central argument is that a rights-based, ethically grounded, and advocacy-driven framework is essential for creating safe, just, and mentally healthy university environments aligned with the vision of NEP 2020 and the constitutional guarantee of life with dignity.